Usos do solo na reforma do canavial: atributos físicos de latossolos, produtividade e qualidade da cana-de-açúcar no 3° corte - Vizioli, Bruno [UNESP] (2014)
The cultures diversification in retirement provides benefits to the sugar cane field soil structure and enhances the productivity of the next culture cycle. The objective of this study was to evaluate the physical characteristics of two Oxisols 30 months after the reform of the sugar plantation uses and productivity of the third cutting cane sugar. The experiment was conducted in two areas, an eutroferric Red Latosol and Acric Latosol, both located in Jaboticabal (SP). The design was a randomized block with five replications and four treatments, the treatments being distinct land uses during the renovation of the sugar plantation, the uses were: soybean / millet / soybean, soybean / sunn hemp / soybean, soybean / fallow / soybeans and soy. The variables analyzed in both soils were: organic matter content, the index of aggregate stability , bulk density, penetration resistance , macro and microporosity and total porosity in layers from 0.00 to 0.10 , 0.10 to 0 20 ; 0.20 to 0.40 and from 0.40 to 0.60 meters. The aggregate of the weighted average of the two soil layers was determined diameter from 0.00 to 0.10 and from 0.10 to 0.20 meters. Productivity and technological parameters of the third cutting of sugar cane were not affected by land use during the reform of the sugar plantation. The aggregation of the two Oxisols, 30 months after the reform of the sugar plantation, was not altered. Treatment soybean/fallow/soybeans yielded less density and penetration resistance and higher porosity in the Red Acrudox 30 months after the reform of the sugar plantation. Single soybean gave higher total porosity and lower bulk density in the Red Acrudox 30 months after the reform of the sugar plantation